Arab Republic of Egypt : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Arab Republic of Egypt. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that Egypt's economic performance since 2004 has been generally impressive, underpinned by a supportive external environment and the structural reform program that has included the liberalization of foreign trade, investment, and the exchange market. Executive Directors have commended the Egyptian authorities for their sound macroeconomic management and economic reforms to date. Executive Directors have also supported the authorities' fiscal policy aimed at striking a balance between bolstering short-term activity and ensuring medium-term fiscal sustainability.